Mesoscale characterization of osseointegration around an additively manufactured genistein-coated implant - Micheletti, Chiara; DiCecco, Liza-Anastasia; Deering, Joseph; Chen, Wanqi; Ervolino da Silva, Ana Cláudia [UNESP]; Shah, Furqan A.; Palmquist, Anders; Okamoto, Roberta [UNESP]; Grandfield, Kathryn (Springer Nature, 2024)
Given the hierarchical nature of bone and bone interfaces, osseointegration, namely the formation of a direct bone-implant contact, is best evaluated using a multiscale approach. However, a trade-off exists between field of view and spatial resolution, making it challenging to image large volumes with high resolution. In this study, we combine established electron microscopy techniques to probe bone-implant interfaces at the microscale and nanoscale with plasma focused ion beam-scanning electron microscopy (PFIB-SEM) tomography to evaluate osseointegration at the mesoscale. This characterization workflow is demonstrated for bone response to an additively manufactured Ti-6Al-4V implant which combines engineered porosity to facilitate bone ingrowth and surface functionalization via genistein, a phytoestrogen, to counteract bone loss in osteoporosis. SEM demonstrated new bone formation at the implant site, including in the internal implant pores. At the nanoscale, scanning transmission electron microscopy and energy-dispersive X-ray spectroscopy confirmed the gradual nature of the bone-implant interface. By leveraging mesoscale analysis with PFIB-SEM tomography that captures large volumes of bone-implant interface with nearly nanoscale resolution, the presence of mineral ellipsoids varying in size and orientation was revealed. In addition, a well-developed lacuno-canalicular network and mineralization fronts directed both towards the implant and away from it were highlighted.
Keywords: LCN; Mineral ellipsoid; Osseointegration; PFIB-SEM tomography; Resin cast etching; Scanning transmission electron microscopy